Effects of solid-state fermented wheat bran by Bacillus amyloliquefaciens and Saccharomyces cerevisiae on growth performance and intestinal microbiota in broiler chickens - Po Yun Teng; Che Lun Chang; Chung Ming Huang; Shen Chang Chang; Tzu Tai Lee (Italian Journal of Animal Science, 2017)
This study evaluated the effects of 10% solid-state fermentation (SSF) wheat bran (WB) by Bacillus amyloliquefaciens (BA) and Saccharomyces cerevisiae (SC) in broiler diets, on growth performance, intestinal morphology, and intestinal microbiota and serum characteristics of broiler chickens. The results showed that fermented wheat bran with BA or BA and SC reduced NDF and ADF contents in WB material. A total of 240 male broilers (Ross 308) were randomly allocated into four feeding groups: (1). Basal diet with 10% WB (control treatment). (2). Basal diet that replaced WB with fermented WB by BA (FWBA). (3). Fermented WB by SC (FWSC), and (4). Fermented WB by BA and SC (FWBA + SC), each group was fed these particular diets for 35 d. Results demonstrated that replacement of WB with FWBA and FWBA + SC improved feed conversion ratio (d 1 to d 35) compared to the control group. Moreover, the 10% FWBA group significantly enhanced the lactic acid bacteria count in the ileum of 35 d old broilers. Compared to the control group, the 10% FWBA and 10% FWSC groups, showed significantly increased ileal lactic acid levels, and in the 10% FWSC group, the ileum villus height was significantly increased in 35 d old broilers. However, treatments with 10% FWBA and 10% FWBA + SC had a tendency to reduce serum cholesterol. In conclusion, a 10% FWBA replacement in the diet could ameliorate health status in broilers by improving growth performance, modulating intestinal microbiota and increasing lactic acid in the ileum.